Re-association of Body Parts: Illusory Ownership of a Virtual Arm Associated With the Contralateral Real Finger by Visuo-Motor Synchrony - Kondo, Ryota; Tani, Yamato; Sugimoto, Maki; Minamizawa, Kouta; Inami, Masahiko; Kitazaki, Michiteru (Frontiers in Robotics and AI, 2020)
Illusory ownership can be induced in a virtual body by visuo-motor synchrony. Our aim was to test the possibility of a re-association of the right thumb with a virtual left arm and express the illusory body ownership of the re-associated arm through a synchronous or asynchronous movement of the body parts through action and vision. Participants felt that their right thumb was the virtual left arm more strongly in the synchronous condition than in the asynchronous one, and the feeling of ownership of the virtual arm was also stronger in the synchronous condition. We did not find a significant difference in the startle responses to a sudden knife appearance to the virtual arm between the two synchrony conditions, as there was no proprioceptive drift of the thumb. These results suggest that a re-association of the right thumb with the virtual left arm could be induced by visuo-motor synchronization; however, it may be weaker than the natural association.